Thank You Fossil Fuels and Good Night : The 21st Century's Energy Transition - Meehan, Gregory, 1954- (Book collections on Project MUSE., 2017)
"This book presents an overview of where we stand on the planet and where we might go in pursuit of energy as fossil fuels are abandoned. Presenting data derived from many government; industry; and academic sources, the book illuminates limitations and problems with various energy sources, most notably with now-untenable reliance on fossil fuels, and shows that internationally, different answers are proving viable for different social and environmental contexts. The goals of the book are logical explanation, reader comprehension, and comprehensive coverage, rather than advocacy"--Provided by publisher